Pengaruh Harga Jual Brand Image Terhadap Minat Beli Produk Makeup Barenbliss Di Jakarta Utara - Dewi Iklima Agustin; Meidiana (JAMBIS : Jurnal Administrasi Bisnis, 2025)
The beauty industry, particularly makeup products, has experienced rapid growth in Indonesia, dominated by South Korean brands such as Barenbliss. The strong K-Beauty phenomenon and the increasing popularity of these products necessitate understanding factors influencing consumer purchase intention. This study investigated the influence of selling price and brand image on consumers’ purchase intention of Barenbliss makeup products in North Jakarta. A quantitative approach with a causal-associative design was employed. Data were obtained through questionnaires administered to 115 female respondents. The analysis included tests for validity, classical assumptions, and hypotheses using SPSS version 24. The results revealed that both selling price and brand image exert a positive and significant effect on purchase intention, both individually and jointly. The coefficient of determination (R²) of 0.813 indicated that 81.3% of the variance in purchase intention is explained by these two variables, with brand image emerging as the most influential factor. Keywords: Selling Price, Brand Image, Purchase Intention